Epistemological and Ontological Dimensions of the Yellow Rice Throwing Tradition in the Wedding Procession in Banyuurip Village, Tuban Regency - Anam, Khoirul (QURU’: Journal of Family Law and Culture, 2023)
Banyuurip village and its people adhere to the religion of their ancestors, which is thick with customs. Often referred to as abangan society before the arrival of the waliyullah who spread Islam. Marriage as a symbol of Javanese custom with a thick procession is the throwing of yellow rice. Not only that, there are also kembang mayang, kacar kucur, sungkeman and others such as things that need to be prepared in marriage such as carrying out the recording of a pre-marital agreement so that if later something unwanted happens so that it can be resolved in a family manner and not dispute deeply with the aim of achieving sakinah mawaddah warohmah. The purpose of making this article is none other than to find out the traditions that exist in Banyuurip Village from the perspective of epistemology and ontology.  This research is a field research with a qualitative method with a philosophical approach by obtaining data by observation, and interviews. The results of this study indicate that the tradition of throwing yellow rice ontologically is that throwing yellow rice symbolizes feelings of affection, then Kembang mayang unites two different hearts with the same taste, while kacar kucur as a daharan symbol of gratitude and Sungkeman as a form of devotion to parents. As for the epistemological aspect, the tradition of throwing yellow rice in the marriage tradition cannot be separated from the influence of the inheritance from the ancestors, which has collaborated with Islamic teachings brought by walisongo and other guardians. In Tuban, there is Sunan Bonang, Sunan Jogobelo, Sheikh Asmoroqondi and other guardians.